Performance of high and low book-to-market stocks with strong financial signals: Evidence in Asia markets 1991-2002 - KANG, Choong Seok Joseph (Institutional Knowledge at Singapore Management University, 2003)
Motivated by striking findings in recent US studies on return enhancing role in financial signals, we examine in the context of Asian stock markets if we can improve one- and two-year returns of high and low book-to-market (BTM) portfolios by retaining in the portfolios only the stocks whose current accounting/financial information indicates strong financial performance in the prior year. We find that doing so can substantially improve the future returns of such portfolios in all markets except Malaysia. We also find that a zero-investment winner-loser strategy on high BTM stocks (a strategy of longing the value stocks with strong financial signals and simultaneously shorting the value stocks with weak financial signals) generates average returns ranging from 5% (Taiwan) to 20% (Korea) with 16% (Singapore) being the median, whereas the zero-investment strategy on low BTM stocks generates average returns ranging from 7% (Korea) to 25% (Taiwan) with 17% (Thailand) being the median. These findings suggest, among other things, that current (hence, outdated) accounting/financial information can contain substantial pricing information on the future returns of both value and glamour stocks also in Asian markets.